Synthesis of the aggregation pheromone of Tribolium castaneum - Biyu An; Xueyang Wang; Ao Jiao; Qinghua Bian; Jiangchun Zhong (Beilstein Journal of Organic Chemistry)
Tribolium castaneum Herbst is a destructive stored product pest. The aggregation pheromone of this pest was prepared via a new and effective strategy. The key steps include the ring-opening reaction of chiral 2-methyloxirane, the stereospecific inversion of chiral secondary tosylate, Li2CuCl4-catalyzed coupling of tosylate with Grignard reagent, and oxidation with RuCl3/NaIO4.